Incidence, recurrence and cost of hyperglycaemic crises requiring emergency treatment in Andalusia, Spain. Issue 7 (11th April 2017) - Barranco, R. J.; Gomez‐Peralta, F.; Abreu, C.; Delgado‐Rodriguez, M.; Moreno‐Carazo, A.; Romero, F.; de la Cal, M. A.; Barranco, J. M.; Pasquel, F. J.; Umpierrez, G. E.
Abstract: Aims: Hyperglycaemic crises (diabetic ketoacidosis and hyperosmolar hyperglycaemic state) are medical emergencies in people with diabetes. We aimed to determine their incidence, recurrence and economic impact. Methods: An observational study of hyperglycaemic crises cases using the database maintained by the out‐of‐hospital emergency service, the Healthcare Emergency Public Service (EPES) during 2012. The EPES provides emergency medical services to the total population of Andalusia, Spain (8.5 million inhabitants) and records data on the incidence, resource utilization and cost of out‐of‐hospital medical care. Direct costs were estimated using public prices for health services updated to 2012. Results: Among 1 137 738 emergency calls requesting medical assistance, 3157 were diagnosed with hyperglycaemic crises by an emergency coordinator, representing 2.9 cases per 1000 persons with diabetes [95% confidence intervals (CI) 2.8 to 3.0]. The incidence of diabetic ketoacidosis was 2.5 cases per 1000 persons with diabetes (95% CI 2.4 to 2.6) and the incidence of hyperosmolar hyperglycaemic state was 0.4 cases per 1000 persons with diabetes (95% CI 0.4 to 0.5). In total, 17.7% ( n = 440) of people had one or more hyperglycaemic crisis. The estimated total direct cost was €4 662 151, with a mean direct cost per episode of €1476.8 ± 217.8. Conclusions: Hyperglycaemic crises require high resource utilization of emergency medical services and have a significant economic impact on the health system. What's new?: Hyperglycaemic crises are medical emergencies in people with diabetes. The overall incidence of hyperglycaemic crises was 2.9 cases per 1000 persons with diabetes during 2012. A total of 17.7% of people exhibited recurrent episodes and 23.9% combined diabetic ketoacidosis and a hyperosmolar hyperglycaemic state. Recurrence was significantly associated with female sex. The estimated total direct cost was €4 662 151, with a mean direct cost per episode of €1476.8 ± 217.8. Hyperglycaemic crises require high resource utilization of emergency medical services, and have a significant economic impact on the health system.